Syntheses and characterization of cyclodiphosphazanes and macrocyclodiphosphazanes - Shi, Xiaoyan (2018)
Organic frameworks have been extensively studied during past decades for a myriad of applications. While inorganic frameworks, composed of non-carbon backbones, remain as mere chemical curiosities due to the much greater kinetic lability of the inorganic bonds. In particular, the instability of cyclodiphosphazane systems contain-ing saturated P-N frameworks, which are of significant interest to our group, has pre-viously undermined the exploration of their use in technological applications. In this thesis, the author firstly represents a convenient method to enhance the stabili-ties of these cyclodiphosphazanes by simply oxidizing them with chalcogen elements on the phosphorus centers (chapter 3). In addition, the author also reported the unexpected C-N bond activation occurred during the oxidation process. The experi-mental and theoretical studies demonstrate that steric factors, most probably steric strain release, play a crucial role in the metal-free activation of the C–N bonds herein described (chapter 4). Besides, conventionally, syntheses of cyclodiphosphazanes has no tolerance of protic solvents stemming from their high air- and moisture-sensitivities. Therefore, the con-cept of mechanochemistry has brought the prospect of avoiding the tedious processes associated with the demand of strict anhydrous conditions while synthesizing cy-clodiphosphazanes. In chapter 5, the first example of cyclodiphosphazanes synthesized by mechanochemical methodology is reported, further studies on the ap-plication of grinding to synthesize a series of new cyclic and acyclic cyclodiphos-phazane frameworks is investigated. More importantly, this method enabled the for-mation of previously reported as inaccessible arrangement adamantoid P4(NtBu)6. Lastly, a family of novel trimeric acyclic poly-cyclodiphosphazanes have been reported in chapter 6. For those structures, their special conformation might enable them as a potential large bite ligand with possible application of stabilizing the low coordination numbers and/or unusual oxidation states transition metal by applying the steric demanding principle. Finally moreover most importantly, inspired by the tri-meric structures, as far as we know, the ever big macrocycle with all P(III) centers, O-bridged hexamer {(μ-O)[P(μ-NtBu)]2}6, has been synthesized and fully characterized.